2011
DOI: 10.1002/ieam.248
|View full text |Cite
|
Sign up to set email alerts
|

Secondary poisoning risk assessment of terrestrial birds and mammals exposed to Nickel

Abstract: The European Union's Existing Substances regulation (EEC 793/93) was developed to assess the ecological risks posed by chemical substances such as Ni and includes the assessment of secondary poisoning risks. The basic structure of this secondary poisoning risk assessment followed the Technical Guidance Document on Risk Assessment and thus included development of predicted exposure concentrations (PECs) and predicted no-effect concentrations (PNECs). A PEC to PNEC ratio greater than 1.0 is indicative of potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…However, the Ni concentration in the snails was always below that in periphyton and macrophytes, the snail BAFs were lower than the periphyton and macrophyte BCF, and the snail biomagnification factor was always below 1, all of which indicates that biomagnification did not occur in this part of the food chain (periphyton to snails). This conclusion is consistent with an analysis of Ni biomagnification potential for terrestrial food webs . McGeer et al report in their meta‐analysis of metal bioconcentration data a trend of increased Ni body concentrations with increased exposure concentration for aquatic organisms.…”
Section: Discussionsupporting
confidence: 84%
“…However, the Ni concentration in the snails was always below that in periphyton and macrophytes, the snail BAFs were lower than the periphyton and macrophyte BCF, and the snail biomagnification factor was always below 1, all of which indicates that biomagnification did not occur in this part of the food chain (periphyton to snails). This conclusion is consistent with an analysis of Ni biomagnification potential for terrestrial food webs . McGeer et al report in their meta‐analysis of metal bioconcentration data a trend of increased Ni body concentrations with increased exposure concentration for aquatic organisms.…”
Section: Discussionsupporting
confidence: 84%
“…Snails are also regarded as key components of terrestrial food webs, and they may contribute to the transfer of pollutants from soil and plants to top predators (de Vaufleury et al, 2006). Earthworms are commonly tested in bioaccumulation studies, because they have a high exposure potential to chemicals in soil, and are important part of diet to a variety of wildlife species (DeForest et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that soil properties, other than metal concentrations, can influence trace metal accumulation in plants and animals. For example, DeForest et al () observed an inverse relationship between Ni BAFs for earthworms and soil Ni concentrations, as well as between BAFs and soil cation exchange capacity (CEC). Similarly, Pauget et al () found that inclusion of pH and CEC into regression models allowed a significantly better prediction of Cd and Pb concentrations in snail tissue than those derived using metal concentration alone.…”
Section: Exposure Estimation In the Usepa Eco‐ssls And Under Reachmentioning
confidence: 99%
“…The source of many of the limitations associated with applying the secondary poisoning assessment to metals is that the guidance was developed with organic contaminants in mind. Metal‐specific guidance has been developed (ECHA ), and this guidance recognizes many of the steps that DeForest et al () used in their refinement of the Ni secondary poisoning assessment.…”
Section: Exposure Estimation In the Usepa Eco‐ssls And Under Reachmentioning
confidence: 99%